Design and development of a non-contact robotic gripper for tissue manipulation in minimally invasive surgery - Ertürk, Şenol; Erzincanlı, Fehmi (Acta Biomedica Atenei Parmensis, 2020)
This paper describes the design and testing of a gripper developed for handling of delicate and flexible tissues during minimally invasive surgery. The device operates on the Bernoulli principle for generating hight-speed flow between the gripper and product surface threby creating vacuum which lifted the product. The Bernoulli gripper, which is widely employed in automated production lines, is a pneumatic manipulator capable of non contact gripping. This study experimentally investigates the applicable of Bernoulli gripper in minimally invasive surgery. The gripper allow tissues to be lifted with minimal contact thereby reducing the possibility of damaging the object. Most of the roobot grippers are not easily applicable in minimal invasive surgery due to the tissues are often delicate, easily damaged, adhesive and slippery. Due to surgeons can not gauging the force exerted on the grasped tissue during laparoscopic grasping, excessive grasp forces may lead to tissue damage. Although Minimally invasive surgery has many benefit, force feedback or touch sensation is limited during th operation in the currently available tools, creating the potential for excessive force application and unintended tissue injury. To overcome such problems, this paper proposes a concept to enable the use of non-contact grippers instead of traditional grippers. In this paper, an innovative approach of a gripper for grasping variable in sizes, shape and weight of chicken tissues are presented. The experimental results show that the Bernoulli principle gripper can be used to lift tissues of different texture and shape without damage. The main objective of this study is to highlights the importance of a non-contact end effector in Minimally invasive surgery and develop a gripper to grasp different tissues. A novel gripper such as the tested prototype has the potential to be used as grasper instrument in minimally invasive surgery. The results will be valuable for literature and future works.